Group algebras whose unit group is locally nilpotent - Victor Bovdi; Бовді Віктор; Bódi Viktor (Cambridge University Press, 2020)
Abstract. We present a complete list of groups G and fields F for which: (i) the group of normalized units V(FG) of the group algebra FG is locally nilpotent; (ii) the set of nontrivial nilpotent elements of FG is finite and nonempty, and V(FG) is an Engel group.
https://www.cambridge.org/core/journals/journal-of-the-australian-mathematical-society/article/abs/group-algebras-whose-unit-group-is-locally-nilpotent/482C5F244EBD8211FAFC0A920468E758
Keywords: unit group; group algebra; locally nilpotent group; Engel group; egységcsoport; csoportalgebra; lokálisan nilpotens csoport; Engel csoport